Gauging the impact of literacy and educational background on receptive vocabulary test scores. (April 2022) - Deygers, Bart; Vanbuel, Marieke
The Peabody Picture Vocabulary Test (PPVT) is a widely used test of receptive vocabulary, but no researchers to date have examined the performance of low-educated, low-literate L2 adults, or compared these individuals' performances to their more highly educated peers. In this study, we used many-facet Rasch analysis and mixed-effects linear regression to determine the impact of educational background and other demographic variables on PPVT test performance. The analyses rely on the performance data of 1, 014 adult learners of Dutch as a second language on the Dutch version of the PPVT (PPVT-III-NL). The results show that a substantial proportion of score variance can be attributed to educational background variables and to the educational tracks the participants followed. These tracks, which cater to the needs of different L2 learner profiles, appear to exacerbate rather than mediate any performance differences. Although this study provides evidence of performance differences and differential item functioning resulting from linguistic, demographic, and educational variables, it offers no data to invalidate the use of the PPVT on low-educated L2 adults.